Investigation of Gene Sequence Divergence, Expression Dynamics, and Endocrine Regulation of the Vitellogenin Gene Family in the Whiteleg Shrimp Litopenaeus vannamei - Wang, Wei; Li, Bin; Zhou, Tingting; Wang, Chenggui; Kyei, Amankwah Beatrice; Shi, Lili; Chan, Siuming (Frontiers in Endocrinology, 2020)
In this report, we studied the vitellogenin gene family in the whiteleg shrimp Litopenaeus vannamei by transcriptomics, bioinformatics and molecular biology methods. At least 3 moderately homologous vitellogenin (Vg) genes (i.e. LvVg1, LvVg2 and LvVg3) were identified in the genome. The deduced LvVg proteins consisted of a vitellogenin_N domain, a DUF1943 domain and a VWD domain typical of most vitellogenins from oviparous animals. LvVg1 was the most abundant Vg expressed in the hepatopancreas and ovary of maturing females. Furthermore, multiple isoforms of LvVg1 were evolved presumably due to the need for rapid Vg production during the rapid phase of vitellogenesis. LvVg transcripts were detected in different larval stages, juveniles and subadults. During the non-reproductive cycle, LvVg expression in the hepatopancreas peaked at the intermolt stages. During the female vitellogenesis cycle, a two-phase expression pattern of LvVg1 gene was observed in the hepatopancreas and ovary. Moreover, the eyestalk optic nerve, brain and thoracic ganglion consisted of factors that differentially regulated the expression of the three Vg genes. In addition to their reproduction-related roles, Vg may also be involved in growth and molt-related processes. Phylogenetic analysis revealed the early expansion and separation of these Vg genes, and it is most likely correlated with the expansion of Vg’s function. In conclusion, the evolution of multiple LvVg1 isoforms and the acquisition of different Vg genes (i.e. LvVg2 and LvVg3) may occur universally in most decapods. Full information on the total number of Vg genes and precise knowledge on the expression pattern and endocrine regulation of each Vg during all life cycle stages are crucial for us to understand the roles of this emerging gene family in the control of shrimp reproduction and other non-reproductive processes.